The Influence Of Video Advertising, Social Media Content, And KOL ( Key Opinion Leader) With Brand Awareness As A Mediation Variable On Purchase Decisions (A Study Of Coffee Shop Businesses In Greater Bandung) - Tubagus Fariz Maulana; Horas Djulius; Undang Juju (Yayasan Pendidikan Belajar Berdikari, 2026)
This study provides an empirical analysis of the digital promotion triad—comprising video advertisements, social media content, and key opinion leaders—and its influence on consumer purchase decisions, using brand awareness as a mediating variable within the coffee shop industry of Greater Bandung, Indonesia.1 Utilizing a descriptive and verification survey design, the study sampled 270 respondents using the Slovin formula, distributed proportionally across five regional districts: Bandung City, Cimahi City, Bandung Regency, West Bandung Regency, and Sumedang Regency.1 Data analysis was executed using Structural Equation Modeling through LISREL 8.8.1 The descriptive results showed high performance for video advertisements, social media content, and brand awareness, while key opinion leaders and purchase decisions fell within the moderate-to-good category.1 Structural estimation confirmed that the digital triad simultaneously influenced brand awareness ( ) and purchase decisions ( ).1 Partially, all three independent variables exerted positive and significant effects on both brand awareness and purchase decisions.1 Brand awareness was found to be a highly critical determinant of purchase decisions and acted as a significant partial mediator, indicating that cognitive brand recognition and recall processes remain crucial for translating digital marketing exposures into actual transactions.1 Triangulation with expert qualitative judgment emphasized the practical necessity of sensory-driven video creation, strategic content scheduling, compliance with regional sweet beverage nutritional labeling (Nutri-Level) policies, and proactive intellectual property registration